2015
DOI: 10.1007/s40272-015-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Migraine in Children and Adolescents

Abstract: While it has been established that headaches in the pediatric age group are relatively common, the characterization of headache disorders and their treatment in this group has historically been limited. Due to the paucity of controlled studies on prophylaxis of the primary headache disorders in children, the diagnosis of migraine often rests on criteria similar to those used in adults. Data from adult studies are often extrapolated and applied to the pediatric patient. Although it appears that many prophylacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Patients taking amitriptyline are warned that the drug may cause drowsiness; therefore, we try to start with a low dose. Topiramate is given to children aged 12 years or older; it is not FDA‐approved for use in younger patients . We avoid giving it to children with a low body mass index because it reduces appetite, and to children with a suspected psychiatric comorbidity, such as depression, because it may increase suicidality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients taking amitriptyline are warned that the drug may cause drowsiness; therefore, we try to start with a low dose. Topiramate is given to children aged 12 years or older; it is not FDA‐approved for use in younger patients . We avoid giving it to children with a low body mass index because it reduces appetite, and to children with a suspected psychiatric comorbidity, such as depression, because it may increase suicidality.…”
Section: Methodsmentioning
confidence: 99%
“…Topiramate is given to children aged 12 years or older; it is not FDA-approved for use in younger patients. 7 We avoid giving it to children with a low body mass index because it reduces appetite, and to children with a suspected psychiatric comorbidity, such as depression, because it may increase suicidality. Patients are warned about other side effects of topiramate, namely lack of concentration, drowsiness, nervousness, and dizziness.…”
Section: Methodsmentioning
confidence: 99%
“…If improvement is seen, we recommend continuing the medication in an attempt to reach a patient‐centered overall treatment goal of fewer than 1 headache per week . If this goal is attained, the patient can be continued on the medication for another few months and then efforts should be made to wean off the medication …”
Section: Recommendations On When To Consider Clinical Use Of Anti‐cgrmentioning
confidence: 99%
“…44,45 When ibuprofen and acetaminophen are not effective in aborting a migrainous headache, or if the headaches are long-lasting and require repeated dosing, migraine specific medications, particularly the triptans, can be administered. Erickson 29 performed an observational study of adult soldiers with posttraumatic headaches, 96% of which demonstrated migrainous features, who were given triptans for abortive management of their headaches.…”
Section: Posttraumatic Headachementioning
confidence: 99%